Characterization of the ion-amorphization process and thermal annealing effects on third generation SiC fibers and 6H-SiC - Huguet-Garcia Juan; Jankowiak Aurélien; Miro Sandrine; Podor Renaud; Meslin Estelle; Thomé Lionel; Serruys Yves; Costantini Jean-Marc (EPJ Nuclear Sciences & Technologies, 2015)
The objective of the present work is to study the irradiation effects on third generation SiC fibers which fulfill the minimum requisites for nuclear applications, i.e. Hi-Nicalon type S, hereafter HNS, and Tyranno SA3, hereafter TSA3. With this purpose, these fibers have been ion-irradiated with 4 MeV Au ions at room temperature and increasing fluences. Irradiation effects have been characterized in terms of micro-Raman Spectroscopy and Transmission Electron Microscopy and compared to the response of the as-irradiated model material, i.e. 6H-SiC single crystals. It is reported that ion-irradiation induces amorphization in SiC fibers. Ion-amorphization kinetics between these fibers and 6H-SiC single crystals are similar despite their different microstructures and polytypes with a critical amorphization dose of ∼3 × 1014 cm−2 (∼0.6 dpa) at room temperature. Also, thermally annealing-induced cracking is studied via in situ Environmental Scanning Electron Microscopy. The temperatures at which the first cracks appear as well as the crack density growth rate increase with increasing heating rates. The activation energy of the cracking process yields 1.05 eV in agreement with recrystallization activation energies of ion-amorphized samples.